MAXIM ANALYSIS OF TEACHER LUKE PODCAST ON YOUTUBE - Nisfia Laili Nizar; Aliva Rosdiana (IKIP Siliwangi, 2024)
Communication must be delivered smoothly and clearly in order to be understood. Communication that follows the principle of good quality conversation. Speakers communicate effectively by providing accurate and concise information. This study employed Grice's cooperative principle. This study sought to identify: 1) types of conversation maxims, 2) categories of conversation maxims, and 3) the purpose of conversation maxims as seen in the Luke Podcast's first episode on YouTube. The researchers employed qualitative research methods. The goal of this research was to use document analysis to identify the maxims issue in Luke Podcast one episode from the YouTube script. According to research, there are four types of conversational maxims: quantity, quality, relation, and manner.